Daya Antifungi Ekstrak Etanol Daun Beluntas - Putri, Rengganis Krisna; Habib, Inayati (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2007)
One of herbal medicine candidate which in developing as antifungal is Pluchea indica, L. Its leaves believed can cure the cough, decrease the fever and also body odor, increase the appetite and also facilitate the digestion. The contain of the leaves are flavonoid, essential oil and saponin that are supposed to have antifungal activity towards Malassezia sp. Tinea versicolor is an infection in human caused by Malassezia, sp. The study aims to determine antifungal activity of the ethanol extract of Pluchea indica leaves against Malassezia, sp.and compare with Ketoconazole as a positive control. The research on antifungal activity of the ethanol extract of Pluchea indica leaves against Malassezia, sp. has been conducted. An examination towards minimal inhibitory concentrations (MIC) and minimal fungicidal concentrations (MFC) is done to determine antifungal activity. MIC of ethanol extract of P. indica leaves and Ketoconazole were determined by macro-broth dilution method, while MFC were determined by cell culture on SDA (Sabaroud Dextrose Agar) plate. First concentration of ethanol extract of P. indica leaves was 25 % and Ketoconazole was 50 %. All of the examination were repeated three times. The result shows that both of MIC and MFC of the ethanol extract of P. indica leaves are 3,125 %. The MIC and MFC of Ketoconazole are 6,25 %. In conclusion, the ethanol extract of P. indica leaves has a higher antifungal activity against Malassezia, sp. than Ketoconazole.Obat tradisional yang mungkin dapat dikembangkan sebagai anti jamur adalah beluntas (Pluchea indica, L). Daun beluntas dipercaya berkhasiat sebagai penurun panas, obat batuk, penghilang bau keringat, menambah nafsu makan (stomakik) dan membantu pencernaan. Daunnya mengandung flavonoid, saponin dan minyak atsiri yang diduga memiliki daya antifungi terhadap Malassezia, sp.. Malassezia, sp.. Tinea versikolor adalah infeksi pada manusia yang disebabkan oleh Malassezia, sp. .Tujuan penelitian ini adalah untuk mengetahui adanya daya antifungi ekstrak etanol daun beluntas (P. indica, L.) terhadap Malassezia, sp. dan perbandingan daya antifungi ekstrak daun beluntas dan Ketokonazole terhadap Malassezia, sp. Daya antifungal dikaetahui dengan pengujian terhadap kadar hambat minimal (KHM) dan kadar bunuh minimal (KBM) ekstrak daun beluntas terhadap jamur. KHM ekstrak daun beluntas diukur dengan menggunakan metode dilusi cair, sedangkan pengukuran KBM dilakukan dengan kultur sel pada media SDA (SabaroudDextrose Agar). Konsentrasi awal ekstrak daun beluntas (P. indica, L.) sebesar 25 % dan Ketokonazole sebesar 50 %. Semua pengujian dilakukan sebanyak tiga kali pengulangan. Hasil penelitian menunjukkan bahwa nilai KHM dan KBM ekstrak daun beluntas (P indica, L.) keduanya sebesar 3,125 %. Ketokonazole mempunyai KHM dan KBM keduanya sebesar 6,25 %. Kesimpulan penelitian adalah ekstrak daun beluntas (P indica, L.) mempunyai daya antifungi terhadapMalassezia, sp. lebih besar dibandingkan dengan Ketokonazole.